Supply chain differentiation, contract agriculture, and farmers' marketing preferences: the case of sweet pepper in Thailand - Christin Schipmann; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2011)
There is an emerging body of literature analyzing how smallholder farmers in developing countries can be linked to modern supply chains. However, most of the available studies concentrate on farm and farmer characteristics, failing to capture details of institutional arrangements between farmers and traders. Moreover, farmers' preferences have rarely been considered. Here, we address these gaps by analyzing different market channels for sweet pepper in Thailand. Using data from a survey and choice experiment with farmers, we find that there is a general preference for marketing options that do not involve a contract. Additional provision of inputs and credit can increase the attractiveness of contracts. Yet, the most important factor for farmers is to personally know the buyer they deal with, which may be related to issues of trust. Some policy implications are discussed.
Keywords: L14; O31; Q12; Q13; 330; Choice experiment; contract design; farmers' stated preferences; modern agricultural supply chains; Thailand